2020
DOI: 10.1037/rev0000189
|View full text |Cite
|
Sign up to set email alerts
|

Theory of neural coding predicts an upper bound on estimates of memory variability.

Abstract: Observers reproducing elementary visual features from memory after a short delay produce errors consistent with the encoding-decoding properties of neural populations. While inspired by electrophysiological observations of sensory neurons in cortex, the population coding account of these errors is based on a mathematical idealization of neural response functions that abstracts away most of the heterogeneity and complexity of real neuronal populations. Here we examine a more physiologically grounded model based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 78 publications
(190 reference statements)
0
10
0
Order By: Relevance
“…We have shown that adapting this model to achieve a higher degree of biophysical realism-by introducing heterogeneity in neural tuning curves and correlated spiking activity-improved the quality of fit to behavioral data. It has recently been shown that more neurally realistic population coding models preserve the key characteristics of the idealized model, and that signatures of neural tuning may even be visible in behavioral data (43).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that adapting this model to achieve a higher degree of biophysical realism-by introducing heterogeneity in neural tuning curves and correlated spiking activity-improved the quality of fit to behavioral data. It has recently been shown that more neurally realistic population coding models preserve the key characteristics of the idealized model, and that signatures of neural tuning may even be visible in behavioral data (43).…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited number of trials for the two invalid conditions, which can make the modelling results less reliable. Furthermore, recent papers have questioned whether the lapse rate is representative of a lack of information when responding (Schurgin et al, 2020;Taylor & Bays, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The first concerns the noise distribution, with TCC using a Gaussian and Neural Resource a Poisson process to describe the system’s stochasticity. While Poisson noise provides a more accurate approximation to neuronal population activity (e.g., Softky & Koch, 1993), it can also be closely approximated by Gaussian noise with an appropriate scaling of variability, and a variant of the Neural Resource model using this approximation has been shown previously to provide a similar account of WM recall errors (Schneegans & Bays, 2017; Taylor & Bays, 2020). Secondly, the two models use different decoding rules, with TCC using the MAX rule (i.e., a “winner-takes-all” decision rule) and Neural Resource using the maximum likelihood decoder.…”
Section: Discussionmentioning
confidence: 99%